Colonization by Enterobacteriaceae is crucial for acute inflammatory responses in murine small intestine via regulation of corticosterone production. (1st November 2020) - Menezes-Garcia, Zélia; Do Nascimento Arifa, Raquel Duque; Acúrcio, Leonardo; Brito, Camila Bernardo; Gouvea, Júlia Oliveira; Lima, Renata Lacerda; Bastos, Rafael Wesley; Fialho Dias, Ana Carolina; Antunes Dourado, Luana Pereira; Bastos, Leandro F. S.; Queiroz-Júnior, Celso Martins; Igídio, Carlos Eduardo Dias; et al.
ABSTRACT: Although dysbiosis in the gut microbiota is known to be involved in several inflammatory diseases, whether any specific bacterial taxa control host response to inflammatory stimuli is still elusive. Here, we hypothesized that dysbiotic indigenous taxa could be involved in modulating host response to inflammatory triggers. To test this hypothesis, we conducted experiments in germ-free (GF) mice and in mice colonized with dysbiotic taxa identified in conventional (CV) mice subjected to chemotherapy-induced mucositis. First, we report that the absence of microbiota decreased inflammation and damage in the small intestine after administration of the chemotherapeutic agent 5-fluorouracil (5-FU). Also, 5-FU induced a shift in CV microbiota resulting in higher amounts of Enterobacteriaceae, including E. coli, in feces and small intestine and tissue damage. Prevention of Enterobacteriaceae outgrowth by treating mice with ciprofloxacin resulted in diminished 5-FU-induced tissue damage, indicating that this bacterial group is necessary for 5-FU-induced inflammatory response. In addition, monocolonization of germ-free (GF) mice with E. coli led to reversal of the protective phenotype during 5-FU chemotherapy. E. coli monocolonization decreased the basal plasma corticosterone levels and blockade of glucocorticoid receptor in GF mice restored inflammation upon 5-FU treatment. In contrast, treatment of CV mice with ciprofloxacin, that presented reduction of Enterobacteriaceae and E. coli content, induced an increase in corticosterone levels. Altogether, these findings demonstrate that Enterobacteriaceae outgrowth during dysbiosis impacts inflammation and tissue injury in the small intestine. Importantly, indigenous Enterobacteriaceae modulates host production of the anti-inflammatory steroid corticosterone and, consequently, controls inflammatory responsiveness in mice.